2013
DOI: 10.1590/s1983-40632013000200003
|View full text |Cite
|
Sign up to set email alerts
|

Lixiviação de potássio proveniente do termopotássio

Abstract: As perdas de potássio no solo, por percolação ou lixiviação, podem ser reduzidas com o emprego de fontes menos solúveis. Objetivou-se avaliar as perdas por lixiviação do potássio proveniente do cloreto de potássio (KCl) granulado e do termopotássio farelado fino e termopotássio granulado. O delineamento utilizado foi inteiramente casualizado, com três repetições, em esquema fatorial com quatro fontes (testemunha, KCl granulado, termopotássio farelado fino e termopotássio granulado) e dois tipos de solo (Neosso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 8 publications
2
11
0
12
Order By: Relevance
“…K is retained with less energy in soil colloids when compared to Ca and Mg, allowing its easy movement in the soil profile (Souza et al, 2012;Duarte et al, 2013), which justifies the greater uniformity of K contents in the different soil layers when compared to Ca and Mg, which decreased with depth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…K is retained with less energy in soil colloids when compared to Ca and Mg, allowing its easy movement in the soil profile (Souza et al, 2012;Duarte et al, 2013), which justifies the greater uniformity of K contents in the different soil layers when compared to Ca and Mg, which decreased with depth.…”
Section: Resultsmentioning
confidence: 99%
“…This may have occurred due to the joint action of several factors such as soil texture and water infiltration, which vary according to the different hillside positions (Lima et al, 2015). In addition, soil K concentration (> 0.40 cmolc dm −3 ), which is considered as high (Faria et al, 2007) and its relative mobility in the soil profile (Souza et al, 2012;Duarte et al, 2013), associated with variations of organic matter content and CEC in the different soil layers (Table 1), may have been important in this interaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Duarte, Pereira and Korndofer (2013) when studying the leaching of potassium in soils under different sources of fertilizers, the highest leaching levels occurred with sources of KCl, but Laurindo et al (2010) in studies about the distribution of this nutrient in the soil via fertigation observed that the K concentration in the soil is reduced when outside the range of the wet bulb.…”
Section: Resultsmentioning
confidence: 99%
“…A mobilidade do íon potássio diminui com o aumento da densidade de cargas negativas nos coloides do solo (Ernani et al, 2007), o que, consequentemente, diminui sua lixiviação pelo perfil (Duarte et al, 2013). Portanto, nas camadas em que os teores de MO foram maiores que 10 g kg -1 (Tabela 6), os teores de K + retido foram maiores, o que confirma o importante papel da MO na retenção do elemento no solo.…”
Section: Resultsunclassified